Re-Emargence of Susceptibility to Conventional First Line Drugs in Salmonella Typhi and Paratyphi a Isolated from Enteric Fever Patients in a Tertiary Care Hospital of Northern Bangladesh. (Bangladesh Journal of Medical Microbiology, 2017)
Enteric fever is endemic in Bangladesh and involves significant health care cost. The first-line drugs chloramphenicol and co-trimoxazole have not been the part of empirical therapy for decades due to development of multidrug resistant Salmonella strains. The objective of this study was to determine the antibiogram pattern of Salmonella strains isolated from the blood of clinically suspected enteric fever patients. A cross sectional study was conducted in Rajshahi Medical College Hospital & Dhaka Medical College from August 2014 to July 2015. Total 323 blood samples were collected from suspected enteric fever patients and isolation rate of Salmonella was 9.29% [S.typhi (3.41%), and S.paratyphi A (5.88%)]. Among isolated S.typhi, 9.09% were resistant to chloramphenicol, cotrimoxazole and cefixime and there were no S.typhi resistant to azithromycin and cefotaxime. Among the isolated S.paratyphi A, 5.26% were resistant to chloramphenicol, co-trimoxazole, azithromycin, cefotaxime, and cefixime. There were no ceftriaxone resistant Salmonella. Low proportion of resistance to first line antibiotics (chloramphenicol, co-trimoxazole) suggests that these drugs can be used once again.Bangladesh J Med Microbiol 2017; 11 (1): 3-5